A Performance-Based Incentives System for Village Health Workers in Kisoro, Uganda - Crystal Y. Zheng; Sam Musominali; Gloria Fung Chaw; Gerald Paccione (Ubiquity Press, 2019)
Background: Village health worker (VHW) programs in Uganda have achieved limited success, due in part to a reliance on volunteerism and a lack of standardized incentive mechanisms. However, how to best incentivize VHWs remains unclear. Doctors for Global Health developed a performance-based incentives (PBI) system to pay its VHWs in Kisoro, Uganda, based on performance of tasks or achievement of targets. Objectives: 1. To describe the development of a PBI system used to compensate VHWs. 2. To report cost and health services delivery outcomes under a PBI system. 3. To provide qualitative analysis on the successes and challenges of PBI. Methods: Internal organization records from May 2016 to April 2017 were retrospectively reviewed. The results of descriptive and analytic statistics were reported. Qualitative analysis was performed by the authors. Findings: In one year, 42 VHWs performed 23,703 remunerable health actions, such as providing care of minor ailments and chronic disease. VHWs earned on average $237. The total cost to maintain the program was $29,844, or $0.72 per villager. There was 0% VHW attrition. Strengths of PBI included flexibility, accountability, higher VHW earnings, and improved monitoring and evaluation. Conclusions: PBI is a feasible and sustainable model of compensating VHWs. At a time where VHW programs are sorely needed to address limitations in healthcare resources, yet are facing challenges with workforce compensation, PBI may serve as a model for others in Uganda and around the world.